Hand kinematics: Application in clinical practice - Santosh Rath (Indian Journal of Plastic Surgery)
Pathological conditions of the hand consequent to injuries, paralysis, disease, arthritis and congenital difference results in loss or limitation of function, deformities, stiffness, inadequate power and poor position for pinch. The pathogenesis of deformities is influenced by bio-mechanical principles of joints and muscle function. The crippling impact of secondary changes due to edema, soft tissue contractures, muscle shortening and functional adaptations also have a mechanical basis. For clinicians and hand therapists, it is necessary to understand these fundamental principles of biomechanics to plan treatment modalities. Interpretation of mechanics of hand deformities in rheumatoid arthritis and paralysis will enable the treating team to identify the appropriate interventions of splinting, therapy and surgical procedures. Basic knowledge of the principles of hand clinical bio-mechanics will help the beginner to sail through the multitude of tendon transfers described in the text books of hand surgery and find the best solution for a particular clinical presentation. Similarly, knowledge of bio-mechanics will provide solutions to an experienced surgeon to plan treatment protocols for complex situations. The article presents a concise summary of the basic principles of hand bio-mechanics for common hand conditions seen in clinical practice. Understanding and applying these principles will help clinicians in planning and devising treatment options for common and complex hand conditions.